The Mechanism of NMDA Receptor Hyperexcitation in High Pressure Helium and Hyperbaric Oxygen - Bliznyuk, Alice; Hollmann, Michael; Grossman, Yoram (Frontiers in Physiology, 2020)
Professional divers exposed to pressures greater than 1.1 MPa may suffer from the high pressure neurological syndrome (HPNS). Divers who use closed-circuit breathing apparatus face the risk of CNS hyperbaric oxygen toxicity (HBOTox). Both syndromes are characterized by reversible CNS hyperexcitability, accompanied by cognitive and motor deficits. Previous studies have demonstrated that the hyperexcitability of HPNS is induced mainly by NMDA receptors (NMDARs). In our recent studies, we demonstrated that the response of NMDARs containing GluN1+ GluN2A subunits was increased by up to 50% at high pressure (HP) He, whereas GluN1+ GluN2B NMDARs response was not affected under similar conditions. Our aim was to compare the responses of both types of NMDARs under HBOTox conditions to those of HP He and to reveal their possible underlying molecular mechanism(s). The two combinations of NMDARs were expressed in Xenopus leavis oocytes, placed in a pressure chamber, voltage-clamped, and their currents were tested at 0.1(control) -0.54 MPa 100% O2 or 0.1-5.1 MPa He pressures. We show, for the first time, that NMDARs containing the GluN2A subunit exhibit increased responses in 100% O2 at a pressure of 0.54 MPa, similar to those observed in 5.1 MPa He. In contrast, the GluN1+GluN2B response is not sensitive to either condition. We discovered that neither condition produced statistically significant changes in the voltage-dependent Mg2+ inhibition of the response. The averaged IC50 remained the same, but a higher [Mg2+]o was required to restore the current to its control value. The application of TPEN, a Zn2+ chelator, in control, HPHeand HBOTox conditions, revealed that the increase in GluN1+GluN2A current is associated with the removal of the high-affinity voltage-independent Zn2+ inhibition of the receptor. We propose that HPNS and HBOTox may share a common mechanism, namely removal of Zn2+ from its specific binding site on the N-terminal domain of the GluN2A subunit, which increases the pore input-conductance and produces larger currents and consequently a hyperexcitation.